The allocation of Greenhouse Gas emission in European Union through applying the claims problems approach - Foroogh Salekpay (Games, 2023)
Due to the challenge of global warming, the European Union (EU) signed the Paris Agreement (2015) to diminish total Greenhouse Gas (GHG) emissions. This paper addresses the conflict that EU member states face when they want to follow the target of the Paris Agreement for the period 2021-2030 which is a 55% GHG emission reduction by 2030 (compared with GHG emission in 1990). EU member states have to emit at a level that is lower than their emission needs. To solve this problem, we implement the claims problems approach as a method for distributing insufficient resources among parties with greater demands. We use several well-known division rules to divide the emission budget among EU member states. We define a set of principles that should be satisfied by division rules to select the most optimal allocation method. To diminish the effect of countries' preferences on the allocation we use equity and stability criteria to examine the fairness of the rules. Moreover, we allocate the emission budget in two ways: First, we apply division rules to allocate the total emission budget for 2021-2030 among countries. Second, we allocate the emission budget annually from 2021 to 2030. We propose that Constrained Equal Awards (CEA) is an appropriate division rule to meet the target of 2030.
Keywords: 330; claims problems; bankruptcy problems; Paris Agreement; climate change